ANALISA KOMPUTASIONAL EFISIENSI UNJUK KERJA PROPELLER DENGAN VARIASI KECEPATAN INLET DAN RPM - Rifki Priandika (2022)
Propeller is an important component to move the ship and is the main function of the ship's propulsion system. Propeller efficiency is very influential on the performance of the ship. This study aims to compare the value of thrust, torque, and propeller efficiency with variations in inlet speed and rpm. In this analysis, the CFD (Computational Fluid Dynamics) method is used to obtain the propeller thrust and torque values. The results of the simulated thrust and torque values will be entered into the efficiency equation. From the results of the CFD simulation by varying the inlet speed and rpm, it can be concluded that the biggest propeller thrust value is located at 230 rpm with an inlet speed of 1 m/s which is 9399.72 N and the biggest propeller efficiency value is located at 190 rpm with an inlet speed of 3 m/s. which is equal to 0.602.